2023
DOI: 10.4401/ag-8986
|View full text |Cite
|
Sign up to set email alerts
|

Lower-ionosphere anomalies prior to strong earthquakes that occurred in north-central mainland Greece on March 2021 as revealed by multi-method analysis of VLF sub-ionospheric propagation data

Dimitrios Z. Politis,
Stelios M. Potirakis,
Yiannis Contoyiannis
et al.

Abstract: In this work we present the multi-method analysis of very low frequency (VLF) data, acquired by the radio receiver with call name UWA, located in Athens (Greece), in the University of West Attica, focusing on two strong ( ) earthquakes (EQs) that occurred in north-central mainland Greece sequentially, on 3 and 4 March 2021, with very close epicenters. Specifically, we used the data acquired from seven VLF transmitters located in Europe, North/North-West to UWA, and their propagation paths include the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…The database includes detailed annotations and metadata, enabling precise analysis and interpretation of the recorded ECG signals. Extensive prior studies have demonstrated that ECG data share several similarities with EMF data [ 25 , 26 ]. Additionally we include another EMF dataset, “Data4”, which was collaboratively obtained [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The database includes detailed annotations and metadata, enabling precise analysis and interpretation of the recorded ECG signals. Extensive prior studies have demonstrated that ECG data share several similarities with EMF data [ 25 , 26 ]. Additionally we include another EMF dataset, “Data4”, which was collaboratively obtained [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Swarm satellite constellation, comprising satellites Alpha, Beta, and Charlie [ 26 ], operates with distinct orbits: A and C travel at an altitude of approximately 450 km in parallel, while B orbits at around a 550 km altitude, perpendicular to Alpha and Charlie. These satellites record Vector Field Magnetometer (VFM) readings, capturing three-axis bounded values denoted as , , and .…”
Section: Quantitative Experimentsmentioning
confidence: 99%